2018 IEEE International Symposium on Information Theory (ISIT) 2018
DOI: 10.1109/isit.2018.8437494
|View full text |Cite
|
Sign up to set email alerts
|

A Precise Analysis of PhaseMax in Phase Retrieval

Abstract: Recovering an unknown complex signal from the magnitude of linear combinations of the signal is referred to as phase retrieval. We present an exact performance analysis of a recently proposed convex-optimization-formulation for this problem, known as PhaseMax. Standard convex-relaxation-based methods in phase retrieval resort to the idea of "lifting" which makes them computationally inefficient, since the number of unknowns is effectively squared. In contrast, PhaseMax is a novel convex relaxation that does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The PhaseLamp method has superior recovery performance over PhaseMax, but again it does not work when δ < 2 for real-valued models. A recent paper [38] extends the asymptotic analysis of [21] to the complex-valued setting, and it was shown that PhaseMax cannot work for δ < 4. On the other hand, AMP.A proposed in this paper achieves perfect recovery when δ > 1.5 and δ > 2.5, for the real and complex-valued models respectively.…”
Section: Existing Theoretical Workmentioning
confidence: 99%
“…The PhaseLamp method has superior recovery performance over PhaseMax, but again it does not work when δ < 2 for real-valued models. A recent paper [38] extends the asymptotic analysis of [21] to the complex-valued setting, and it was shown that PhaseMax cannot work for δ < 4. On the other hand, AMP.A proposed in this paper achieves perfect recovery when δ > 1.5 and δ > 2.5, for the real and complex-valued models respectively.…”
Section: Existing Theoretical Workmentioning
confidence: 99%
“…For our analysis, we utilize the recently developed Convex Gaussian Min-max Theorem (CGMT) [31] which is a strengthened version of a classical Gaussian comparison inequality due to Gordon [10], and whose origins are in [26]. Previously, the CGMT has been successfully applied to derive the precise performance in a number of applications such as regularized M-estimators [30], analysis of the generalized lasso [19,31], data detection in massive MIMO [1,2,32], and PhaseMax in phase retrieval [6,24,23].…”
Section: Summary Of Contributionsmentioning
confidence: 99%
“…Theorem 3 (CGMT). [29] In (24), let S w , S u , be convex and compact sets, and assume ψ(•, •) is convexconcave on S w × S u . Also assume that G, g, and h all have entries i.i.d.…”
Section: A Convex Gaussian Min-max Theorem (Cgmt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, [14], [15] proposed a convex optimization based algorithm for solving the phase retrieval problem that doesn't lift the underlying signal and hence does not square the number of variables. The precise analysis of it has been derived in [16], [17]. Typical non-convex approaches involve finding a good initialization, followed by iterative minimization of a loss function.…”
Section: Prior Workmentioning
confidence: 99%